Strategi Pembelajaran Inovatif di Era Digital: Meningkatkan Kualitas Pendidikan Abad ke-21 - Widyastuti, Zohra; Rokot, Ridwan Arke (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2025)
The development of digital technology has brought significant changes in the world of education, demanding the adoption of innovative learning strategies to improve the quality of education in the 21st century. This research aims to analyze the effectiveness of technology-based learning strategies in improving student learning outcomes and identify challenges in their implementation. This study uses a descriptive qualitative method approach to scientific articles published in the last five years. Literature sources come from reputable journals that discuss the integration of technology in learning, including artificial intelligence, gamification, and adaptive learning. The results of the study show that the use of technology in learning, such as blended learning, gamification, and artificial intelligence, is able to increase student engagement and understanding. However, challenges in implementing this strategy include limited infrastructure, low digital competence of educators, and resistance to change. The research also highlights that the development of digital skills for educators and the optimization of digital education infrastructure are indispensable to support the success of innovative learning strategies. These findings imply the need for more adaptive policies in the application of educational technology, including strengthening training for educators and investing in digital facilities and infrastructure. With the right approach, innovative learning strategies can contribute to increasing the effectiveness and efficiency of education in the digital era.AbstrakPerkembangan teknologi digital telah membawa perubahan signifikan dalam dunia pendidikan, menuntut adopsi strategi pembelajaran inovatif guna meningkatkan kualitas pendidikan abad ke-21. Penelitian ini bertujuan untuk menganalisis efektivitas strategi pembelajaran berbasis teknologi dalam meningkatkan hasil belajar peserta didik serta mengidentifikasi tantangan dalam implementasinya. Studi ini menggunakan metode kualitatif deskriptif. Sumber literatur berasal dari jurnal bereputasi yang membahas integrasi teknologi dalam pembelajaran, termasuk kecerdasan buatan, gamifikasi, dan pembelajaran adaptif. Hasil penelitian menunjukkan bahwa pemanfaatan teknologi dalam pembelajaran, seperti blended learning, gamifikasi, dan kecerdasan buatan, mampu meningkatkan keterlibatan serta pemahaman peserta didik. Namun, tantangan dalam implementasi strategi ini meliputi keterbatasan infrastruktur, rendahnya kompetensi digital pendidik, serta resistensi terhadap perubahan. Penelitian juga menyoroti bahwa pengembangan keterampilan digital bagi pendidik dan optimalisasi infrastruktur pendidikan digital sangat diperlukan untuk mendukung keberhasilan strategi pembelajaran inovatif. Temuan ini mengimplikasikan perlunya kebijakan yang lebih adaptif dalam penerapan teknologi pendidikan, termasuk penguatan pelatihan bagi pendidik serta investasi dalam sarana dan prasarana digital. Dengan pendekatan yang tepat, strategi pembelajaran inovatif dapat berkontribusi pada peningkatan efektivitas dan efisiensi pendidikan di era digital.